A survey of the sorghum transcriptome using single-molecule long reads - Salah E. Abdel-Ghany (Nature Portfolio, 2016)
Alternative splicing and alternative polyadenylation (APA) contribute to mRNA diversity but are difficult to assess using short read RNA-seq data. Here, the authors use single molecule long-read isoform sequencing and develop a computational pipeline to identify full-length splice isoforms and APA sites in sorghum.